2010
DOI: 10.4049/jimmunol.0902589
|View full text |Cite
|
Sign up to set email alerts
|

Absence of SHIP-1 Results in Constitutive Phosphorylation of Tank-Binding Kinase 1 and Enhanced TLR3-Dependent IFN-β Production

Abstract: Autoimmune diseases, such as systemic lupus erythematosus and rheumatoid arthritis, result from a loss of tolerance to self-antigens and immune-mediated injury precipitated by the overproduction of type I IFN and inflammatory cytokines. We have identified the inositol 5′ phosphatase SHIP-1 as a negative regulator of TLR3-induced type I IFN production. SHIP-1–deficient macrophages display enhanced TLR-induced IFN-β production, and overexpression of SHIP-1 negatively regulates the ability of TLR3 and its adaptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 50 publications
2
65
0
Order By: Relevance
“…This results in hydrolyzation of the phosphatidylinositol 3-kinase (PI3K)-generated second-messenger PI-3,4,5-P3 (PIP3) to PI-3,4-P2 (38). In mice, SHIP1 has been shown to be a negative regulator of IFN-␤ production and lipopolysaccharide (LPS)-induced antibacterial response (39,40). Hence, we hypothesized that during JEV infection, SHIP1 is involved in mediating miR-155-induced IFN-␤ signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in hydrolyzation of the phosphatidylinositol 3-kinase (PI3K)-generated second-messenger PI-3,4,5-P3 (PIP3) to PI-3,4-P2 (38). In mice, SHIP1 has been shown to be a negative regulator of IFN-␤ production and lipopolysaccharide (LPS)-induced antibacterial response (39,40). Hence, we hypothesized that during JEV infection, SHIP1 is involved in mediating miR-155-induced IFN-␤ signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Further, TBK-1 plays an essential role in TLR-and RIG-I-mediated induction of IFN-␣/␤ and host antiviral responses by regulating activation of NF-B and IRFs (47)(48)(49). In addition, SHIP1 negatively regulates IFN-␤ expression by targeting TBK-1 (40). To further correlate induction of miR-155 with regulation of SHIP1, IRFs, and NF-B activation during JEV infection, we evaluated the in vitro and in vivo effects of inhibiting miR-155 on expression of phosphorylated and total IRF3/7, TBK-1, and phosphorylated NF-B.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, a number of molecules that curtail TLRmediated IFN-b induction have been identified, including TAG, Ro52/TRIM21, and SHIP-1 (13)(14)(15). Regarding the TLR adaptor molecules themselves, until quite recently, the physiological role of these adaptors was considered to be facilitation of TLR activation and concomitant perpetuation of the signaling cascade.…”
mentioning
confidence: 99%
“…Further investigation revealed that SHP-2 actually interacts with TBK1 and blocks its kinase activity, thus attenuating signalling to IRF3 [107]. Another molecule, the inositol 5' phosphatase (SHIP-1), also interacts with TBK1, negatively regulating production of IFN following TLR3 stimulation [108].…”
Section: Modulation Of Signalling Downstream Of Trifmentioning
confidence: 99%